Preservice Chemistry Teachers Preconception on the Topic of Sustainable Development Oriented Plant Pigments Separation - Murti*, Adek Diah; Hernani, Hernani; Fatimah, Soja Siti; Nursiwan, Wimbi Apriwanda (Universitas Syiah Kuala, 2023)
One of the important principles in the success of learning activities is that educators need to pay attention to students' preconceptions before designing learning designs, because this will provide direction in compiling learning materials and strategies to achieve learning goals. This study aims to identify the preconceptions of preservice chemistry teachers as a basis for developing a didactic design on the topic of plant pigments separation which is one of the materials discussed in analytical chemistry II lectures. This research uses descriptive methods with participants were 36 pre-service chemistry teachers at one of the state universities in Pekanbaru City. This descriptive study used a diagnostic test in the form of an essay which totaled 19 questions. Based on the results of preconception analysis, it was identified that most of the students experienced learning barriers mostly in the following sub-discussions: (1) types of green solvents; (2) benefits of eutectic solvents; (3) the relationship of eutectic solvent with principles of green chemistry; (4) the process of making eutectic solvents; (5) experimental stages of plant pigment extraction; (6) processes that occur during extraction; and (7) extraction techniques. So it can be concluded that students do not yet have sufficient basic knowledge because students are not yet able to answer questions in most contexts on the topic of separating plant pigments